A non‐invasive approach to enumerating White Sturgeon (Acipenser transmontanus Richardson, 1863) using side‐scan sonar. (23rd January 2018) - Hughes, J. B.; Bentz, B.; Hightower, J. E.
Summary: Mark‐recapture (M/R) surveys are a standard approach for monitoring White Sturgeon (WS) Acipenser transmontanus populations; however, they can be resource‐intensive, may affect fish health, and often lack enough precision to detect population change reliably. Hydroacoustics surveys provide a non‐intrusive method that is well‐established in fisheries research, but have been applied relatively seldom to sturgeon populations. During 2016, an alternative method was tested for estimating WS abundance by using side‐scan sonar within a 58‐km reach in the middle Snake River, Idaho, USA, and comparing the results to a standard M/R estimate. Using replicate count data within a N‐Mixture model, the sonar method estimated a lower abundance with higher precision (153, 101–213 95% Bayesian credible interval) than that of M/R (219, 138–398 95% confidence interval). Relative to M/R, side‐scan sonar took 75% fewer sample‐days, exhibited overlapping abundance estimates, and provided similar sturgeon length distributions. These results suggest that side‐scan sonar can provide a rapid and precise alternative to M/R for estimating sturgeon abundance.